The Effect of the Earth Science Community Learning Model Assisted By Geographical Tools Learning Media on Student Learning Outcomes in Geography Learning - Abulkhair, M. Faris; Syahrul Ridha; Jummi, Cut Vita Rajiatul (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Geography learning requires active involvement of students in understanding geosphere phenomena contextually and spatially. However, learning that is still focused on teachers has the potential to result in low student understanding, especially in natural resource material. This study aims to determine the effect of the Earth Science in Community (EarthComm) learning model assisted by geographical tools on student learning outcomes in geography learning. This study uses a quantitative approach with a pre-experiment type through a one group pretest-posttest design. The research sample consisted of 20 students in one class at SMAS Methodist Banda Aceh. The research instrument was an objective multiple-choice test administered through pretest and posttest. Data analysis was performed using the Shapiro–Wilk normality test and the paired sample t-test hypothesis test at a significance level of 5%. The results showed that the data were normally distributed and that there was a significant effect of the EarthComm learning model assisted by geographical tools on the understanding of natural resource material, as indicated by a two-tailed significance value ≤ 0.05, namely 0.00000012. Thus, the EarthComm learning model assisted by geographical tools is effective in improving student understanding and is relevant for application in geography learning.